2011
DOI: 10.1177/1367006911425819
|View full text |Cite
|
Sign up to set email alerts
|

Metalinguistic awareness mediates effects of full biliteracy on third-language reading proficiency in Turkish–German bilinguals

Abstract: Bilingualism has been reported to be positively associated with both metalinguistic awareness and third-language (L3) acquisition. In the present research, the assumptions were tested that literacy in both first (L1) and second (L2) language (full biliteracy) is needed for bilingualism to be positively associated with L3 reading proficiency, and that positive effects of full biliteracy on L3 reading proficiency are mediated through metalinguistic awareness. L1, L2 and L3 reading proficiency and metalinguistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 45 publications
1
28
0
3
Order By: Relevance
“…This echoes the early observation of Swain et al (1990) that it is not bilingualism per se that carries benefits for the individual, but literacy in the two languages. Other studies also highlight the importance of literacy for the development of metalinguistic awareness in multilingual populations in different contexts (Rauch, Naumann, & Jude, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This echoes the early observation of Swain et al (1990) that it is not bilingualism per se that carries benefits for the individual, but literacy in the two languages. Other studies also highlight the importance of literacy for the development of metalinguistic awareness in multilingual populations in different contexts (Rauch, Naumann, & Jude, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Research targeting the impact of nonmajority L1 (e.g., Turkish, Russian, or Slovak in the context of Germany) on the learning of a foreign language in school, which would be a third language (L3) for learners studying in L2‐medium contexts, is growing slowly. However, the ability to speak two or more languages alone does not seem to positively impact L3 acquisition, whereas biliteracy in L1 and L2 does (Rauch, ; Rauch, Naumann, & Jude, ). Following the threshold hypothesis (Cummins, ), the (very) early start of foreign language learning may be an obstacle in L2 development for learners with limited L1 proficiency.…”
Section: Learner Characteristics and Their Relationship To L2 Proficimentioning
confidence: 99%
“…Some scholars have suggested that the key to the cognitive advantage reflected in more efficient L3 acquisition is biliteracy, rather than exclusively oral bilingualism (Rauch, Naumann, & Jude, 2012;Sanz, 2008;Swain et al, 1990). Bilinguals illiterate in their L1 do not perform significantly better than their monolingual counterparts.…”
Section: Age and The Bilingual Advantagementioning
confidence: 99%